c+11=11c-19

Simple and best practice solution for c+11=11c-19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for c+11=11c-19 equation:


Simplifying
c + 11 = 11c + -19

Reorder the terms:
11 + c = 11c + -19

Reorder the terms:
11 + c = -19 + 11c

Solving
11 + c = -19 + 11c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-11c' to each side of the equation.
11 + c + -11c = -19 + 11c + -11c

Combine like terms: c + -11c = -10c
11 + -10c = -19 + 11c + -11c

Combine like terms: 11c + -11c = 0
11 + -10c = -19 + 0
11 + -10c = -19

Add '-11' to each side of the equation.
11 + -11 + -10c = -19 + -11

Combine like terms: 11 + -11 = 0
0 + -10c = -19 + -11
-10c = -19 + -11

Combine like terms: -19 + -11 = -30
-10c = -30

Divide each side by '-10'.
c = 3

Simplifying
c = 3

See similar equations:

| X(2x+8)=3x-4 | | 69.4/4 | | 4km2/12k | | 41s-6=38s | | 24b-36=6b | | 0=9w^2-30w+25 | | X(2x+8)=(3x-4) | | 3x-8=44-X | | 8y-11=6y+7 | | 4(2k+1)-18=26 | | 24/x=16 | | 15y+12=11y+20 | | 2cos^2x-sinx-1=0 | | 12(v+4)-3v=3(3v+3)-18 | | 0=4u^2-15u-4 | | 16q-10=14q | | 1/2x-2=2x-1/2 | | 15m+8=10m-7 | | 2p-14=p+16 | | c-3=2c-12 | | -8t=4t+5+2t | | 7.8×9/4 | | 18v=14v+16 | | 1/3x4= | | -10(x)=5-10x | | 6q=10q-16 | | 7=7(5-4) | | 5v-8v-3v-6= | | 18=p-6 | | ax+2=2y | | x+x+x+12+5*x=10*x-2 | | (3x^5/85^4)^-3 |

Equations solver categories